Association Between Atherogenic Indices and the Triglyceride–Glucose Index in Individuals with Obesity - Alakuş, Ömer Faruk; Kılıç, Jehat; Solmaz, İhsan (Sakarya University, 2026)
Objective: Atherogenic indices such as the plasma atherogenic index (AIP) and Castelli ratios provide valuable information about cardiometabolic risk. The triglyceride-glucose (TyG) index, a metabolic indicator of insulin resistance, has also been studied in relation to many metabolic disorders in recent years and is a prominent index in obese individuals. This study aims to evaluate the relationships between these indices and to investigate gender-based differences in obese adults. Methods: This retrospective cross-sectional study included 262 obese adults evaluated at the Internal Medicine outpatient clinic. Demographic and clinical data of the patients were retrospectively obtained from the hospital information management system. Ethical approval was obtained on October 24, 2025 (Decision No. 684), and the study was conducted in accordance with the Helsinki Declaration. Anthropometric data, including height, weight, and waist circumference, were obtained from the patients' medical records. All laboratory parameters were obtained from routine fasting blood samples, known to have been analyzed after at least 8 hours of fasting, from electronic records. Atherogenic indices and the TyG index were calculated using validated formulas. Results: All 262 participants in the study were obese adults without known comorbidities; the mean body mass index was 36.43 kg/m² and the mean waist circumference was 108.35 cm. A significant number of biochemical parameters were within the reference ranges; however, triglycerides, LDL cholesterol, and atherogenic indices were significantly elevated. Significant gender differences were observed; men had higher body weight, waist circumference, kidney enzymes, liver enzymes, triglyceride levels, and all atherogenic indices (all p = 0.001), while women had higher HDL cholesterol and platelet count. Strong and significant positive correlations were found among all indices examined; the strongest correlation was observed between the TyG index and AIP (r = 0.911, p < 0.01). Conclusions: In this study, atherogenic indices showed significant correlations among themselves and significant gender-based differences; a more unfavorable metabolic profile was observed in men. TyG index, a metabolic marker of insulin resistance, showed a strong correlation with AIP; suggesting that the TyG index is strongly associated with AIP and may reflect atherogenic dyslipidemia and early cardiometabolic risk in obese adults. © 2026, Sakarya University. All rights reserved.
Keywords: Atherogenic Index Of Plasma; Castelli Index; Obesity; Triglyceride–Glucose Index